Restoring Conscious Arousal During Focal Limbic Seizures with Deep Brain Stimulation. (3rd March 2016) - Kundishora, Adam J.; Gummadavelli, Abhijeet; Ma, Chanthia; Liu, Mengran; McCafferty, Cian; Schiff, Nicholas D.; Willie, Jon T.; Gross, Robert E.; Gerrard, Jason; Blumenfeld, Hal
Abstract: Impaired consciousness occurs suddenly and unpredictably in people with epilepsy, markedly worsening quality of life and increasing risk of mortality. Focal seizures with impaired consciousness are the most common form of epilepsy and are refractory to all current medical and surgical therapies in about one-sixth of cases. Restoring consciousness during and following seizures would be potentially transformative for these individuals. Here, we investigate deep brain stimulation to improve level of conscious arousal in a rat model of focal limbic seizures. We found that dual-site stimulation of the central lateral nucleus of the intralaminar thalamus (CL) and the pontine nucleus oralis (PnO) bilaterally during focal limbic seizures restored normal-appearing cortical electrophysiology and markedly improved behavioral arousal. In contrast, single-site bilateral stimulation of CL or PnO alone was insufficient to achieve the same result. These findings support the "network inhibition hypothesis" that focal limbic seizures impair consciousness through widespread inhibition of subcortical arousal. Driving subcortical arousal function would be a novel therapeutic approach to some forms of refractory epilepsy and may be compatible with devices already in use for responsive neurostimulation. Multisite deep brain stimulation of subcortical arousal structures may benefit not only patients with epilepsy but also those with other disorders of consciousness.